Marketing Strategy of Bvlgari - Mursalova, Leyli (2023)
My thesis is focused on analyzing the marketing strategy of “Bulgari.” The thesis is divided into theoretical and practical (analytical) sections. The first section outlines the theoretical methods that are advised for use in creating a marketing plan. The practical part will concentrate on choosing the best marketing plan for a product launch that the business should employ. This thesis will be based on primary and desk research regarding the current market size, competitors, and most recent market trends. The aim of my thesis is to describe the ways of marketing improvement of the company “Bulgari,” thus revealing their advantages and disadvantages in order to make a proper choice.